Micropropagación y determinación cromosómica del género Croton productores de látex - Ruiz Ríos y Cols., Astriht (2019)
The present investigation had the purpose of: determining the differences in the in vitro development of buds from croton young plants of latex producers; to evaluate the response to the acclimatization of croton’s plantulas with better behavior in vitro, and to determine the chromosomal number of selected individuals of croton latex producers. The culture medium for the in vitro introduction was determined evaluating the behavior of croton draconoides in five treatments with the basic medium murashige and skoog (ms) taking into consideration that the species in the study belong to the same gender. The buds coming from croton young plants producers of wine latex had the best behavior in the selected culture medium (ms + 0,01mg/i ana + 0,1mg/i of baP and aG3 + 20 ml of coconut water) presenting an increase in height, number of leaves and percentage of survival in relationship to croton producers of red and ocher latex. The plantulas of croton producers of wine latex, previously rooted in vitro, were taken for acclimatization. Four substrates were tested, determining that the response of the plantulas changes according to the substrate composition, watering conditions (nebulization), fungus control (benlate to 0,1%) and the application of the bioestimulant biogen 1 to 0,1%. The chromosomal number determined in plants of the gender croton producers of red, wine and ocher latex was of 40.